Teaching and Learning to Program: Umbrella Review of Introductory Programming in Higher Education - Sónia Rolland Sobral (Mathematics, 2021)
Introductory programming courses in science, technology, engineering, and mathematics (STEM) degrees are critical to student success throughout the students’ academic and professional route but have traditional failure and dropout rates. The number of publications and reviews on the subject is growing, so we realize the need to prepare an umbrella review, or review of reviews, to group previous studies and extract more comprehensive and ambitious results. Based on the databases ACM, Google Scholar, IEEE, SCOPUS and Web of Science libraries, a formal search was created that resulted in 21 reviews on programming fundamentals in higher education context. Results include bibliometric information on the CS1 reviews, in the context of higher education (namely annual evolution, number and information on authors, types and sources of information, countries of affiliation, languages, keywords and most cited articles), the purpose of the reviews and research questions, methods (namely search strategy, databases used, eligibility criteria) and results (number of records and tables or divisions were made to catalog the articles). We present a taxonomy with four different types of purpose: general, specific, student group and teacher directed. We found very interesting catalogs that can serve as a tool for future work, whether by researchers in the field or by authors who intend to carry out reviews related to introduction to programming, especially in the context of higher education.